2021
DOI: 10.1149/1945-7111/ac41f5
|View full text |Cite
|
Sign up to set email alerts
|

The Ag+ Reduction Process in a Plasma Electrochemical System Tuned by the pH Value

Abstract: The interactions between discharge plasmas and an aqueous solutions can enable the production of reactive species and charge transfer at the plasma-liquid interface, forming the plasma electrochemical system (PES). The PES are promising for diverse applications, such as nanomaterials synthesis, due to the activation of the solution chemistry by the plasma. In this paper, we investigate the influence of the solution’s pH value on the formation of silver nanoparticles (AgNPs) in a direct current (DC) PES. Dual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The plasma reduction routes of silver ion ( ) to zero-valent silver ( ) nanoparticles are well established, and are based on the two following reactions [ 5 , 23 , 43 ]: …”
Section: Resultsmentioning
confidence: 99%
“…The plasma reduction routes of silver ion ( ) to zero-valent silver ( ) nanoparticles are well established, and are based on the two following reactions [ 5 , 23 , 43 ]: …”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that both Ag + reduction and oxidation processes occur during AgNP synthesis [46,47]. The e − aq , H, and alcohol fragment radicals are the main reducing agents for Ag + to AgNPs, whereas H 2 O 2 generated by the plasma-liquid interaction oxidises AgNPs to Ag + , as shown in Equation (7).…”
Section: Mechanism Of Plasma Preparation Of Metal Colloidsmentioning
confidence: 99%
“…Through computational studies, we reveal that glycerol can undergo photodissociation of the O−H bonds for incident photon energies of >5 eV, forming various radicals, e.g., hydrogen radicals (H•, with a standard redox potential of −2.3 V), that then exhibit the ability to reduce silver ions (Ag + + H• → Ag 0 + H + ). 28,29 In this study, to differentiate among different plasma species such as electrons, ions, metastables, and UV photons, optical filters were introduced between the plasma and the droplet of the Ag/glycerol electrolyte solution, as depicted in panels a and b of Figure 1. The relevant experimental setup is described in section S1 of the Supporting Information.…”
mentioning
confidence: 99%
“…We find that photons with energies as low as 5 eV deliver an important contribution to NP production, resulting from the fragmentation of glycerol upon UV irradiation composed of these comparatively low-energy photons. Through computational studies, we reveal that glycerol can undergo photodissociation of the O–H bonds for incident photon energies of >5 eV, forming various radicals, e.g., hydrogen radicals (H•, with a standard redox potential of −2.3 V), that then exhibit the ability to reduce silver ions (Ag + + H• → Ag 0 + H + ). , …”
mentioning
confidence: 99%